Mixed projections and syntactic categories - Lowe, J (Cambridge University Press, 2019)
I explore the bases of a ‘distributionalist’ approach to syntactic categories, i.e. an approach which makes distinctions on the basis of purely syntactic (as opposed to, say, semantic) criteria. I focus on the phenomenon of ‘mixed projections’, where a syntactic phrase appears to display properties of more than one syntactic category, as analysed within the framework of Lexical-Functional Grammar. I argue that of the three syntactic criteria called upon in the definition of syntactic categories within this approach only one, the internal syntactic structure of a phrase, is a sufficient criterion for syntactic categorization. This leads to a more restricted definition of category mixing, and implies a more restricted approach to categorization in general